Effects of different storage temperatures and durations on the activity of coagulation factor Ⅷ and Ⅸ in whole blood - WANG Hehe; WANG Tiantian; WANG Jie; QIAO Cuicui; LIU Wei; ZHANG Xueqin; CHENG Yan; FANG Yunhai; ZHANG Xinsheng (Zhongguo shuxue zazhi, 2025)
[Objective] To investigate the effects of different storage temperatures and durations on the activities of coagulation factor Ⅷ (Factor Ⅷ, FⅧ) and coagulation factor Ⅸ (Factor Ⅸ, FⅨ) after whole blood collection, so as to provide data support for the optimal storage conditions. [Methods] A total of 16 mL of whole blood was collected from each of the 20 healthy volunteers at our blood center and aliquoted into 8 sodium citrate anticoagulant tubes. Two tubes were immediately centrifuged for the measurement of FⅧ and FⅨ activity levels. The remaining 6 tubes of whole blood were respectively stored under room temperature and low-temperature conditions. At 2, 4, and 6 h, the whole blood samples were centrifuged and analyzed for FⅧ and FⅨ activity levels. The mean values of the two immediately tested tubes were used as the control group, while other tubes were designated as the experimental groups for comparison. Statistical analysis was performed using SPSS 26.0. [Results] The activity of FⅧ in whole blood remained stable after 4 hours of storage at both room temperature and low temperature (116.53±25.95 vs 125.22±27.33, 109.77±23.23 vs 125.22±27.33) (P>0.05 for both). However, by 6 hours, FⅧ activity showed a statistically significant decline compared to the control group (108.65±22.92 vs 125.22±27.33, 100.46±20.19 vs 125.22±27.33) (P<0.05 for both), though the room temperature group results were closer to the control values. The activity of FⅨ in whole blood remained stable after 6 hours of storage under both conditions (97.14±19.48 vs 96.76±19.67, 97.10±17.45 vs 96.76±19.6) (P>0.05 for all comparisons). [Conclusion] For whole blood samples after collection, storage at either room temperature or low temperature for up to 4 hours does not compromise the accuracy of test results. When stored for 6 hours, FⅨ activity remains stable, whereas FⅧ activity decreases significantly. Notably, FⅧ activity demonstrates better stability at room temperature than under low-temperature conditions within the 6-hour storage.